Hotel and lodging advertisements from Malaysian group buying websites: A genre-based approach / Mohd Safarizan Mohd Safian - Mohd Safarizan, Mohd Safian (2016)
The growth of internet advertising in Malaysia is one of the reasons Malaysians are shifting from face-to-face transaction to online buying. Online advertisers need to promote new, interesting methods to attract customers. One of the methods includes the usage of group buying sites, which provides great deals and offers through online-coupons. Because of this, it would be interesting to see how these group buying sites communicate and persuade readers to read and use their services. This study looks into three main aspects which are the move structure, links on the online advertisements and common linguistic features. The main purpose of this study is to analyze the rhetorical structure and communicative purpose of hotel and lodging online advertisements. This study adopted Askehave and Nielsen’s (2005) two-dimensional model approach as the main framework to analyze the data collected. The usage of this framework accounts for a better explanation on the usage of digital genre as Askehave and Nielsen’s (2005) two-dimensional model approach was used not only for examining the moves in the online advertisements, but also the links involved which provide access to different parts of the web page. In addition, this study also looks at the common linguistic features available in the data collected. Twenty-five different hotel and lodging advertisements were collected from five different group buying sites. From the twenty-five data, each move and link was identified and the frequency of occurrence was tabulated. A move with a frequency of occurrence of more than 50% is known as an obligatory move, whereas moves with an occurrence of less than 50% are optional moves. Also, only links with a frequency of occurrence of at least 50% from the online advertisements were taken into account. Adapting Askehave and Nielsen’s (2005), framework, fifteen (15) moves were identified as obligatory from the data collected which are attracting attention, identifying sender, indicating content structure, establishing credentials, establishing contact, establishing a discourse community, iii promoting an external organization, highlighting important information, detailing description of the deal, indicating terms and condition, promoting service applications, providing related information of the website via links, including choices based on background, rewarding web users and creating an opportunity to feature business. There were also two (2) optional moves which are greeting and detailing (selected) content. On the other hand, the navigating mode shows that generic links were more prevalent than specific links, with a frequency count of nineteen generic links compared to four specific links. In looking into the linguistic features, second person interpersonal pronoun ‘you’ and possessive adjective ‘your’, adjectives, binomial/multinomial expressions, ellipsis and imperatives are identified as the common linguistic features used in the data collected. Different choices of moves, links and linguistic features proves that all these elements are used by the web owners of group buying sites to persuade readers to take action upon the advertisements.